Role of Performance Appraisal System and Its Impact on Employees Motivation - Dangol, Pooja (Yayasan Ahmar Cendekia Indonesia, 2021)
The general objective of the study is to determine the role of performance appraisal and its impact on employee. The study is guided by the following specific objectives: to establish the extent to which performance appraisal process affects employee motivation, to determine the extent to which appraisers affect staff motivation and to determine the challenges in appraising employee performance. The study adopted descriptive research design. The population of interest consists of 120 employees of Service Industry in Nepal. Data is collected using structured questionnaires and additional qualitative data is collected using the reference from the questionnaire and the objectives of the study. The data is analysed using statistical tools such as frequency distribution, percentages and Pearson correlations. Data is presented using tables and charts. The research findings suggest that regular assessment of performance leads to employee motivation. Performance appraisal rating can be considered as a technique that has a positive effect on work performance and employee motivation. Employees may be motivated if the appraisal process is based on accurate and current job descriptions. On the challenges of performance appraisal on employee motivation established that some managers tend to be liberal or strict in their rating of staff which may affect the employees’ motivation. The manager’s ability to address the skills gaps can have a significant impact on the employee’s motivation. Regular ratings may affect the performance and motivation of the employees. Fair assessment of the employee’s performance may enhance their motivation.